2019
DOI: 10.1039/c9nj03275d
|View full text |Cite
|
Sign up to set email alerts
|

Merocyanines based on 1,2-diphenyl-3,5-pyrazolidinedione

Abstract: The acceptor strength of the 1,2-diphenyl-3,5-pyrazolidinedione residue is re-evaluated based on the spectral-fluorescent properties of donor–acceptor dyes. Low fluorescence of the title compounds is explained by the low-lying forbidden ππ*-state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…We conducted systematic investigations of the fluorescence properties of merocyanines for the first time, which allowed us to discover a number of specific features and make generalizations about the electronic symmetry of their chromophore in the fluorescent state S 1 . [67,[69][70][71]73,74,98] Based on the mirror symmetry (likeness) between the absorption and fluorescence (Levshin's law), it could be assumed that the regularities in the fluorescence spectra of merocyanines would be similar to those in their absorption spectra. However, it was found that even typical electronically nonsymmetric merocyanines exhibit fluorescence similar to symmetric ionic polymethines.…”
Section: Fluorescence Spectramentioning
confidence: 99%
See 4 more Smart Citations
“…We conducted systematic investigations of the fluorescence properties of merocyanines for the first time, which allowed us to discover a number of specific features and make generalizations about the electronic symmetry of their chromophore in the fluorescent state S 1 . [67,[69][70][71]73,74,98] Based on the mirror symmetry (likeness) between the absorption and fluorescence (Levshin's law), it could be assumed that the regularities in the fluorescence spectra of merocyanines would be similar to those in their absorption spectra. However, it was found that even typical electronically nonsymmetric merocyanines exhibit fluorescence similar to symmetric ionic polymethines.…”
Section: Fluorescence Spectramentioning
confidence: 99%
“…It was found that the FQYs of 3,5-pyrazolidinedione-based merocyanines comprising indole (62)(63)(64) and benzo[cd]indole (68-70) as donor end-groups are notably inferior to that of their analogs with other strong acceptor groups, such as barbiturate and thiobarbiturate. [74] The PCM/TD-B3LYP calculations revealed that a probable cause for this is the enhancement of internal conversion, which was attributed to the presence of a low-lying 1 π HÀ 1 π L * state associated with a dipole-forbidden transition from HOMO-1, localized on the acceptor 1,2-diphenyl-3,5-pyrazolidinedione fragment, to LUMO. This conclusion was supported by the second-order approximate coupled cluster singles and doubles model (CC2) calculation.…”
Section: Fluorescence Spectramentioning
confidence: 99%
See 3 more Smart Citations